2020
DOI: 10.1101/2020.03.19.998468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sparse long-range connections in visual cortex for cost-efficient small-world networks

Abstract: 9The brain performs visual object recognition using much shallower hierarchical stages than artificial deep 10 neural networks employ. However, the mechanism underlying this cost-efficient function is elusive. Here, 11 we show that cortical long-range connectivity(LRC) may enable this parsimonious organization of circuits 12 for balancing cost and performance. Using model network simulations based on data in tree shrews, we 13 found that sparse LRCs, when added to local connections, organize a small-world n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Currently, DNN models, which have a biologically inspired hierarchical structure, provide an effective approach for investigating functions in the brain ( Paik and Ringach, 2011 ; DiCarlo et al, 2012 ; Yamins and DiCarlo, 2016 ; Sailamul et al, 2017 ; Baek et al, 2020 , 2021 ; Jang et al, 2020 ; Kim et al, 2020 , 2021 ; Park et al, 2021 ; Song et al, 2021 ). Several studies have reported that DNNs trained to natural images can predict the neural responses of the monkey inferior temporal cortex (IT) ( Cadieu et al, 2014 ; Yamins et al, 2014 ), known as the area for object recognition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, DNN models, which have a biologically inspired hierarchical structure, provide an effective approach for investigating functions in the brain ( Paik and Ringach, 2011 ; DiCarlo et al, 2012 ; Yamins and DiCarlo, 2016 ; Sailamul et al, 2017 ; Baek et al, 2020 , 2021 ; Jang et al, 2020 ; Kim et al, 2020 , 2021 ; Park et al, 2021 ; Song et al, 2021 ). Several studies have reported that DNNs trained to natural images can predict the neural responses of the monkey inferior temporal cortex (IT) ( Cadieu et al, 2014 ; Yamins et al, 2014 ), known as the area for object recognition.…”
Section: Methodsmentioning
confidence: 99%
“…A model study using a biologically inspired deep neural network (DNN) ( Krizhevsky et al, 2012 ; Simonyan and Zisserman, 2015 ) has been suggested as an effective approach to this problem ( Paik and Ringach, 2011 ; DiCarlo et al, 2012 ; Yamins and DiCarlo, 2016 ; Sailamul et al, 2017 ; Baek et al, 2020 , 2021 ; Jang et al, 2020 ; Kim et al, 2020 , 2021 ; Park et al, 2021 ; Song et al, 2021 ). DNNs, which consist of a stack of feedforward projections inspired by the hierarchical structure of the visual pathway, can be used as simplified model to investigate various visual functions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, deep neural network (DNN) models, which have a biologically inspired hierarchical structure, provide an effective approach for investigating functions in the brain (Paik and Ringach, 2011;DiCarlo et al, 2012;Yamins and DiCarlo, 2016;Sailamul et al, 2017;Baek et al, 2020Baek et al, , 2021Jang et al, 2020;Kim et al, 2020Kim et al, , 2021Park et al, 2021;Song et al, 2021). Several studies have reported that DNNs trained to natural images can predict the neural responses of the monkey inferior temporal cortex (IT) (Cadieu et al, 2014;Yamins et al, 2014), known as the area for object recognition.…”
Section: Untrained Alexnetmentioning
confidence: 99%
“…A model study using a biologically inspired deep neural network (DNN) (Krizhevsky et al, 2012; Simonyan and Zisserman, 2015) has been suggested as an effective approach to this problem (Paik and Ringach, 2011; DiCarlo et al, 2012; Yamins and DiCarlo, 2016; Sailamul et al, 2017; Baek et al, 2020, 2021; Jang et al, 2020; Kim et al, 2020, 2021; Park et al, 2021; Song et al, 2021). DNNs consist of a stack of feedforward projections inspired by the hierarchical structure of the visual pathway and can be used as simplified model to investigate various visual functions.…”
Section: Introductionmentioning
confidence: 99%